DESIGN DAN PEMBUATAN BRACKET ASSY BULLDOZER - Abdul Muchlis; Sandy Suryady; Ahcmad Risa Harfit (Jurnal Ilmiah Teknik, 2024)
In this century, the industrial sector is a very important sector to support the national economy. The industrial sector contributed very high so that it succeeded in bringing Indonesia to the 85th rank out of 131 countries in the world's manufacturing industry, the industrial sector was growing very rapidly accompanied by increasing positive growth. Bracket assy is a component or frame structure on a bulldozer that uses SS400 and ST37 type steel metal material, which means that the component is very strong and does not break easily when exposed to heavy loads. Bracket assy is a product that has gone through various fabrication processes. The function of the bracket assy is as a handle for the hydraulic system pipe and also the pedestal of the body or engine cover, the bracket assy is located above the front of the car chassis which is positioned facing up. The process of making the bracket assy, namely, the selection of materials used in the process of making the Bracket Assy, namely Steel SS400 and ST 37, Gas Cutting Machines, Bending Machines, and Welding Machines. In the cutting process of the Gas Cutting Machine, the workpiece is cut. Next is the Bending Machine process where the workpiece is bent. Furthermore, the welding process of the workpiece is welded in 2 stages, namely the first tack welding and full welding / Fillet Weld, then Quality Control is carried out to check whether the product is ready to be distributed, the product is qualified into two types, namely GOOD for products that have passed Quality control and NOT GOOD for products that do not pass Quality Control.